REQUIRED GRADUATE ATTRIBUTES IN HONG KONG AND THEIR RELATIVE IMPORTANCE - Li, Tilo (European Scientific Journal, ESJ, 2015)
Massification of higher education in Hong Kong and elsewhere has triggered public’s concern about the possible fall or already falling in its quality. To gauge higher education quality, a set of quantifiable attributes is needed. The purposes of this study are to construct a quality hierarchy for higher education consisting of dimensions, aspects, and items; and prioritize attribute aspects and items among stakeholders – employers, academics and college administrators, college graduates, and tertiary students. A total of 530 questionnaires were collected. Ordinal Likert scale data were converted into interval-ratio logits using Rasch models with the computer software Winsteps. Multidimensionality was found using Rasch analysis and linear factor analysis. Different stakeholder groups had different views on quite a few attributes. For example, employers ranked ‘sense of responsibility and commitment’; academics and graduates ranked ‘problem-solving ability’, and students ranked ‘expression of ideas in oral English’ the most important. This may explain why students at times complain about having to take courses outside their discipline and provides insight to college program developers how to align different perspectives of stakeholders.